Client Psychology - Chaffin, Charles R.; CFP Board Center For Financial Planning (Newark : John Wiley & Sons, Inc., 2018)
If you can get data into Excel, then there is a giant basket of data analysis tools at your fingertips. This handbook shows how to access and use the features and techniques for organizing, manipulating and summarizing just about anything that resides in a worksheet. If you're familiar with Excel but lack a background in the technical aspects of data analysis, this user-friendly book makes it easy to start putting Excel to use for you.
Includes bibliographical references and index.
Keywords: Motion pictures -- Philosophy